DAMPAK DIASPORA TIONGKOK DI INDONESIA TAHUN 2012-2017 - Annisa S, R Harfina; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The aims of this studyis to analyze how the influence of Chinese diaspora in Indonesia. International migration is one of the currents of globalization that causes foreign citizens to enter the Indonesian territory with various backgrounds. The ethnic of Chinese in Indonesiaalready exist for years ago, it is proved by the arrival of the first Chinese Buddhist priest named FaHien in Indonesia who became the beginning of the entrance for the people of China to Indonesia. The existence of Chinese in Indonesia more diverse.In this study, researchers used primary and secondary data. In data collection techniques using interviews, literature study and online search. This writing uses the perspective of globalism and the level of analysis of the international community. The concept used in this study is the concept of diaspora by Vertovec.The results of this study indicate that the spread of Chinese society in Indonesia gives a little impact and influence on the economy, politics, social and culture of Indonesia. This is the evident from the bilateral relations between two countries in addressing the issue of citizenship, the presence of foreign investment in Indonesia that is influential in the state economy, as well as the influence of Chinese social ethnic culture in the Indonesian society.Keywords: International migration, China Diaspora, Perspektif of Globalism, Globalization